Applying a nonparametric efficiency analysis to measure conversion efficiency in Great Britain - Martin Binder; Tom Broekel (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In the literature on Sen's capability approach, studies focussing on the empirical measurement of conversion factors are comparatively rare. We add to this field by adopting a measure of 'conversion efficiency' that captures the efficiency with which individuals convert their re-sources into achieved functioning. We use a nonparametric efficiency procedure borrowed from production theory and construct such a measure for a set of basic functionings, using data from the wave 2006 of the British Household Panel Survey (BHPS). In Great Britain, 49.88% of the individuals can be considered efficient while the mean of the inefficient indi-viduals reaches one fifth less functioning achievement. An individual's conversion efficiency is positively affected by getting older, being self-employed, married, having no health prob-lems and living in the London area. On the other hand, being unemployed, sepa-rated/divorced/widowed and (self-assessed) disabled decrease an individual's conversion effi-ciency.
Keywords: I12; I31; R15; 330; conversion efficiency; welfare measurement; robust nonparametric efficiency analysis; functioning production; Wohlfahrtstheorie; Messung; Lebensstandard; Disparitätsmaß; Technische Effizienz; Nichtparametrisches Verfahren; Robustes Verfahren; Großbritannien